اﻷﺑﻌﺎد اﻟﻔﻨﻴﺔ ﻟﺸﺨﺼﻴﺔ زﻳﻨﺐ ﻓﻲ رواﻳﺔ ﺷﻈﺎﻳﺎ ﺣﺎرﻗﺔ آﻣﻨﺔ ﺑﺮواﺿﻲ - هاجر, حنيش; هدى, فرطاس; خديجة, عروك; أحمد أمين, بن موسى (جامعة الوادي - University of Eloued, 2019)
ﺧﻼﺻﺔ ﻟﻬذﻩ اﻟدراﺳﺔ ﻧرى أن اﻟﺷﺧﺻﯾﺔ ﺗﻌﺗﺑر ﻣن أﻫم ﻣﻛوﻧﺎت اﻟﻌﻣل اﻟرواﺋﻲ، ﺣﯾث ﺗﻌد ﻋﻧﺻر ﻓﻌﺎل ﻓﻲ ﺳرد اﻷﺣداث وﺗﺣرﯾﻛﻬﺎ، وﻟﻠﺷﺧﺻﯾﺔ ﻋدة دﻻﻻت ﻓﻘد ﺗﻧﺎوﻟﻧﺎ ﺷﺧﺻﯾﺔ زﯾﻧب ﻓﻲ رواﯾﺔ ﺷظﺎﯾﺎ ﺣﺎرﻗﺔ ﻵﻣﻧﺔ ﺑرواﺿﻲ، اﻟﺗﻲ ﻛﺎﻧت ﻣن ﺑﯾن اﻟﺷﺧﺻﯾﺎت اﻟﺑﺎرزة ﻓﻲ اﻟرواﯾﺔ وﺣﻣﻠت ﻟﻧﺎ ﺑدورﻫﺎ اﻟﻌدﯾد ﻣن اﻟدﻻﻻت واﻟﻣﻌﺎﻧﻲ ﺳواءا ﻛﺎﻧت ﻟﻐوﯾﺔ، دﯾﻧﯾﺔ أو ﺗﺎرﯾﺧﯾﺔ. Abstract In the conclusion of this study we see that personality is one of the most important components of the novel work, as it is an effective element in the narrative of events and moving, and the personality has several implications, we have dealt with the character of Zeinab in the novel SHADHAYA HAREKA to Amina Broadi, who was among the prominent figures in the novel and carried us in turn many indications Meanings, whether linguistic, religious or historical.
اﻟﺪراﺳﺎت اﻷدﺑﻴﺔ